"TEACHER DRESS AND SPEECH CULTURE" (International conference on multidisciplinary science, 2023)
This scientific article explores the intricate relationship between a teacher's dress and speech culture and its influence on classroom dynamics and the overall educational environment. The way educators present themselves through their attire and verbal communication plays a pivotal role in shaping student perceptions, engagement, and the learning atmosphere. This study delves into the psychological, sociological, and pedagogical aspects of teachers' dress and speech culture, shedding light on its implications for student-teacher relationships, academic performance, and the overall educational experience.